Kepribadian Dan Komunikasi Susi Pudjiastuti Dalam Membentuk Personal Branding - Stevani Stevani; Widayatmoko Widayatmoko (Jurnal Komunikasi, 2017)
The life story of Susi Pudjiastuti is admired by many people for her hard work, until becoming successful by having so much company in the field of aviation and fisheries. Susi Pudjiastuti is also well known to the public for his work in the ministry. Good performance makes Susi Pudjiastuti popular among Jokowi's working cabinet. Currently, the Brand Name in humans is personal branding which is the trend of the formation of self-image and the creation of good perception from others to us. This research will discuss about personality, communication and personal branding Susi Pudjiastuti with qualitative research method. Good personality makes Susi Pudjiastuti has the ability to communicate well and liked by the community. Personality and communication can form a personal branding Susi Pudjiastuti a natural. By exposing the personality and communication of Susi Pudjiastuti in forming personal branding, then people will realize the importance of personality and Communication in forming a natural personal branding. Kisah hidup Susi Pudjiastuti banyak dikagumi oleh banyak orang atas kerja kerasnya hingga menjadi sukses dengan memiliki banyak perusahaan di bidang penerbangan dan perikanan. Susi Pudjiastuti juga dikenal baik oleh masyarakat akan kinerjanya dalam bekerja di kementerian.  Kinerja yang baik menjadikan Susi  Pudjiastuti popular  diantara  kabinet  kerja Jokowi. Saat ini, Sebutan merek pada manusia adalah personal branding yang merupakan trend dari pembentukan  pencitraan diri dan penciptaan persepsi yang baik dari orang lain kepada kita.  Penelitian  ini  akan membahas  mengenai  kepribadian,  komunikasi  serta  personal  branding Susi Pudjiastuti  dengan  metode  penelitian  kualitatif. Kepribadian  yang baik menjadikan Susi Pudjiastuti memiliki kemampuan berkomunikasi dengan baik dan disenangi oleh masyarakat. Kepribadian dan komunikasi tersebut dapat membentuk personal branding Susi Pudjiastuti yang alami. Dengan memaparkan kepribadian dan komunikasi Susi Pudjiastuti dalam membentuk personal branding,   maka masyarakat akan menyadari pentingnya kepribadian dan Komunikasi dalam membentuk personal branding yang natural.